2021
DOI: 10.1186/s13058-021-01452-5
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal doxorubicin promotes migration and invasion of breast cancer cells: role of Src Family non-receptor tyrosine kinases

Abstract: Background Doxorubicin (Dox) is a widely used chemotherapy, but its effectiveness is limited by dose-dependent side effects. Although lower Dox doses reduce this risk, studies have reported higher recurrence of local disease with no improvement in survival rate in patients receiving low doses of Dox. To effectively mitigate this, a better understanding of the adverse effects of suboptimal Dox doses is needed. Methods Effects of sublethal dose of Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 91 publications
(108 reference statements)
8
28
0
Order By: Relevance
“…The treatment of MDA-MB-231 cells with doxorubicin upregulated the expression of N-cadherin (∼3-fold), β-catenin (∼3-fold), and SNAI1 (∼2-fold) and slightly upregulated also the expression of vimentin; in addition, the expression of E-cadherin slightly decreased. These results are consistent and support the view that sub-lethal doses of doxorubicin activate the EMT pathway in breast cancer cells. Thus, these findings confirm that anticancer chemotherapy using doxorubicin is inappropriate as it can cause drug-resistant TNBC cells to metastasize, so the search for new drugs to treat breast cancer that would show better antitumor effects than doxorubicin is justified.…”
Section: Resultssupporting
confidence: 79%
“…The treatment of MDA-MB-231 cells with doxorubicin upregulated the expression of N-cadherin (∼3-fold), β-catenin (∼3-fold), and SNAI1 (∼2-fold) and slightly upregulated also the expression of vimentin; in addition, the expression of E-cadherin slightly decreased. These results are consistent and support the view that sub-lethal doses of doxorubicin activate the EMT pathway in breast cancer cells. Thus, these findings confirm that anticancer chemotherapy using doxorubicin is inappropriate as it can cause drug-resistant TNBC cells to metastasize, so the search for new drugs to treat breast cancer that would show better antitumor effects than doxorubicin is justified.…”
Section: Resultssupporting
confidence: 79%
“…Increased expression of MMP-2 and MMP-9 have been proposed as the prognostic marker in breast cancer 27 . Mohammed et al investigated the effects of sublethal doxorubicin treatment in noninvasive MCF-7 cells and found that doses of 0.6 μM or less of doxorubicin led to increased migration and invasion by increasing the induction and secretion of MMP isoforms, including MMP-2 and MMP-9 28 . The present study showed that 5 μM doxorubicin alone did not change the levels of MMP-2 and MMP-9 in MCF-7 cells, but addition of ozone treatment successfully reduced these levels.…”
Section: Discussionmentioning
confidence: 99%
“…e Bcr-abl fusion gene encodes a pathogenic protein (p210BCR-ABL) that continuously increases tyrosine kinase activity and activates multiple downstream signaling pathways to promote the occurrence and development of myeloid leukemia (chronic myeloid leukemia, CML) [25][26][27]. BCR-ABL kinase is closely related to SRCfamily kinases (SFK), which make up the largest nonreceptor tyrosine kinase family in the human body, including LYN, FYN, LCK, HCK, FGR, BLK, YRK, YES, and c-SRC [28][29][30][31][32][33]. ey play a very important role in regulating cell proliferation, differentiation, adhesion, and movement [34][35][36], and abnormal expression of SFK members is related to the occurrence of various tumors in the human body [37][38][39].…”
Section: Discussionmentioning
confidence: 99%